Alien vs. Predator - Anderson, Paul,|d1965-; O'Bannon, Dan; Shusett, Ronald (Twentieth Century Fox ; distributed in the Philippines by Viva Video, 2004)
The incredible adventure begins when the discovery of an ancient pyramid buried in Antarctica sends a team of scientists and adventures to the forzen continent. There, they make an even more terrifying discovery: two alien races engaged in the ultimate battle. Whoever wins ... we lose.